2008
DOI: 10.1111/j.1743-6109.2007.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox Dividing Testosterone Deficiency Symptoms and Androgen Assays: A Closer Look at the Cellular and Molecular Mechanisms of Androgen Action

Abstract: Introduction Central to the diagnosis and treatment of testosterone deficiency syndrome in the adult male is the remarkable paradox that there is a very poor correlation between the characteristic symptoms and levels of serum androgens. Aim Because androgen deficiency can be associated with severe symptomatology, as well as diverse conditions such as coronary heart disease, diabetes, and metabolic syndrome, the aim was to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 97 publications
(117 reference statements)
1
21
0
Order By: Relevance
“…However it has been found that the AMS scale can be used to measure and compare the health-related quality of life in those of less than 40 years of age on the basis of similar European normative values [16]. The surprisingly high prevalence of raised scores in the younger age groups may be due to the increasing impact of work stress in these age groups, which has been shown to decrease testosterone synthesis [17,18] and increase resistance to its action [19]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However it has been found that the AMS scale can be used to measure and compare the health-related quality of life in those of less than 40 years of age on the basis of similar European normative values [16]. The surprisingly high prevalence of raised scores in the younger age groups may be due to the increasing impact of work stress in these age groups, which has been shown to decrease testosterone synthesis [17,18] and increase resistance to its action [19]. …”
Section: Resultsmentioning
confidence: 99%
“…The uniform and sustained relief of these symptoms given by testosterone treatment has been confirmed by the experience over more than 15 years in 1700 men in the UKAS treated predominantly on the basis of their symptoms rather than androgen levels [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More controversially Carruthers 35 suggests that the symptoms are more important than the biochemistry suggesting that a male may be ‘hypogonadal’ at the tissue level while having a normal T level. Reduced arterial flow and pre‐DHT receptor events are suggested 36 . Proper clinical trails are required to support these suggestions.…”
Section: Diagnosis Of Hypogonadism In the Older Malementioning
confidence: 99%
“…Reduced arterial flow and pre-DHT receptor events are suggested. 36 Proper clinical trails are required to support these suggestions.…”
Section: Diagnosis Of Hypogonadism In the Older Malementioning
confidence: 99%